2007
DOI: 10.1186/1745-7580-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Strength in numbers: achieving greater accuracy in MHC-I binding prediction by combining the results from multiple prediction tools

Abstract: Background: Peptides derived from endogenous antigens can bind to MHC class I molecules. Those which bind with high affinity can invoke a CD8 + immune response, resulting in the destruction of infected cells. Much work in immunoinformatics has involved the algorithmic prediction of peptide binding affinity to various MHC-I alleles. A number of tools for MHC-I binding prediction have been developed, many of which are available on the web.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…This result is consistent with the results reported in the two recent comparison studies (Trost et al, 2007;Lin et al, 2008) where the two servers implementing ARB and SMM (Peters et al, 2006) demonstrated a better performance than Rankpep (Reche et al, 2004) which was implemented using the PSSM method.…”
Section: Comparison Of Qualitative Mhc-i Predictorssupporting
confidence: 91%
“…This result is consistent with the results reported in the two recent comparison studies (Trost et al, 2007;Lin et al, 2008) where the two servers implementing ARB and SMM (Peters et al, 2006) demonstrated a better performance than Rankpep (Reche et al, 2004) which was implemented using the PSSM method.…”
Section: Comparison Of Qualitative Mhc-i Predictorssupporting
confidence: 91%
“…In the end, this would increase the number of predicted epitopes and include peptides with ˃9 amino acid residues [7,8,9] (Data S1). Taken together, mouse-or human-specific epitopes identified in silico hold potential as strong vaccine candidates against cutaneous leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover at present, we can select peptide that bind to HLA-A*0201 molecule by molecular modeling with accumulation of knowledge on the crystal structures of class I molecules and the sequences of peptides of endogenous origin bound by the class I molecules [19]. A comparative evaluation of prediction serves have been reported [20][21][22]. Many studies show we can achieve higher accuracy by combining the results from different prediction tools.…”
Section: Discussionmentioning
confidence: 99%